Development and testing of an iron impregnated activated carbon for the removal of arsenic from ground water - Xaignavong, Langkone (2008)
This study dealt with the experimental investigation related to the removal of arsenic from synthetically contaminated groundwater by batch and column adsorption experiments using different adsorbents in order to compare adsorption capabilities and capacities to reduce concentration of arsenic to levels allowable by international drinking water standards and guidelines. The adsorbents used include commercial granular activated carbon (CGAC), rust and their composite forms, i.e. Fe3+ and rust impregnated CGAC (CGAC-Fe3+, and CGAC-rust, respectively). These adsorbents were characterized by proximate analysis, scanning electron microscopy (SEM), nitrogen adsorption (BET)and X-ray diffraction (XRD) analysses. The treated water was analyzed using an inductively coupled plasma-atomic emmission spectrometer (ICP-AES) and atomic adsorption spectroscopy (AAS). It was found out that impregnating iron, in its iconic form Fe3+, did not cause any observable changes on the physical properties of activated carbon. However, those impregnated with rust, i.e. CGAC-rust composite, showed significant accumulation of maghemite (y-Fe2-O3) and hematite (fe2O3) on the CGAC surface as suggested by the results of microscopy and diffraction analyses. In the removal of arsenite with initial concentration to 20 ppm, impregnation with iron, ionic or in the form of rust, improved the capacity of the adsorbents approximately 10-15 times more in reducing arsenite with initial concentrations to 50 ppb when using continous column testing. Furthermore, these composite adsorbents were able to remove up to 98.5% arsenite, providing an effluent concentration of 28 ppb arsenite in the batch testing experiments. It is interesting to note also that treatment with rust alone was able to reduce arsenite ion in solution from 1,840 ppb to 0.92 ppb (a reduction of 2000 times) at treatment efficiency of 99.95%. It is therefore recommended that further studies be conducted on the kinetics of adsorption using rust and CGAC-rust, which, apparently, are the better adsorbents in this study.